A Systematic Review on the Application of Ontologies to Improve Career Guidance - Dickson Kalungi; Annabella Habinka Ejiri; Fred Kaggwa; Simon Kawuma (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2023)
The review discusses students’ challenges as they move between educational levels and the labor market, mainly due to the lack of effective, efficient, and timely career guidance. The review suggests that using ontologies can improve career guidance delivery by providing a structured approach to representing and organizing career-related data. The study conducted a systematic literature review and found that ontologies have not been extensively applied in the career guidance domain. The review highlights the unique advantages of using ontologies for career guidance (CG), such as formal representation, interoperability, and knowledge representation and reasoning. The review also points out the loopholes in the few studies that attempted to use ontologies in CG. A systematic literature review was carried out to assess the extent to which ontologies have been applied in CG. Four reviewers performed a systematic search in IEEE, Scopus, Web of Science, and google scholar independently using agreed-upon criteria. To eliminate the bias of leaving out important studies, abstracts from selected conferences were carefully screened and reference scanning of the search results was performed. Out of 307 studies, 11 were found to match the search parameters and were included in the study.